2006
DOI: 10.1016/j.abb.2006.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate does not protect macrophages against apoptosis induced by oxidised low density lipoprotein

Abstract: Apoptosis of macrophages and smooth muscle cells is observed in atherosclerotic lesions and may play an important role in the disease progression. Oxidised low density lipoprotein (LDL) is cytotoxic and induces apoptosis in a variety of cell types. We reported previously that ascorbate protects arterial smooth muscle cells from apoptosis induced by oxidised LDL containing the peak levels of lipid hydroperoxides. We now demonstrate that macrophages undergo apoptosis when treated with this species of oxidised LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…These findings are consistent with those reported by Yannarelli et al (2006), in which they found that AsA pretreatment prevented the UV-Binduced up-regulation of HO-1 mRNA in soybean plants. Similar effects of AsA on HO-1 gene expression were also confirmed in animals subjected to oxidized low density lipoprotein (LDL), Cd, chromium (Cr) treatments (Harris et al 2006;Elbekai et al 2007). For example, pretreatment of smooth muscle cells (SMC) with the antioxidant vitamin C attenuated the induction of HO-1 by moderately oxidized LDL (moxLDL) or highly oxidized LDL (oxLDL) compared with cells not pretreated with vitamin C (Anwar et al 2005).…”
Section: Discussionmentioning
confidence: 59%
“…These findings are consistent with those reported by Yannarelli et al (2006), in which they found that AsA pretreatment prevented the UV-Binduced up-regulation of HO-1 mRNA in soybean plants. Similar effects of AsA on HO-1 gene expression were also confirmed in animals subjected to oxidized low density lipoprotein (LDL), Cd, chromium (Cr) treatments (Harris et al 2006;Elbekai et al 2007). For example, pretreatment of smooth muscle cells (SMC) with the antioxidant vitamin C attenuated the induction of HO-1 by moderately oxidized LDL (moxLDL) or highly oxidized LDL (oxLDL) compared with cells not pretreated with vitamin C (Anwar et al 2005).…”
Section: Discussionmentioning
confidence: 59%
“…9 -15,21-25,32,33 Almost all of these studies have shown adverse effect of oxLDL, including cell apoptosis and death. 11,12,24,32,33 Unfortunately, the concentration of oxLDL used in these studies has varied from 10 to 100 g/mL. Although the precise concentration of oxLDL in the tissues is not known, these concentrations are at least 1-log higher than those seen in normal human sera.…”
Section: Discussionmentioning
confidence: 99%
“…LDL (150 µg protein/ml) was oxidised at 37°C by adding CuSO 4 (5 µM net above the calculated final EDTA concentration) in PBS, as described previously [58]. Briefly, the initial absorbance at 234 nm was read and further readings were taken every 15-20 min.…”
Section: Preparation Of Lipid Hydroperoxide-rich Ldlmentioning
confidence: 99%